Evaluasi Kinerja Guru dalam Pembelajaran Bahasa Arab Melalui Kitab Qowa’idul Lughoh Al’Arabiyyah di kelas 3 SMA Qur’anic School of Al-Muthi’ah Sapen Mojolaban Sukoharjo Tahun Ajaran 2024/2025 - Khansa Nabilah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2024)
Arabic language learning plays a crucial role in Islamic education, particularly in understanding the Qur'an. At the Qur'anic School of Al-Muthi'ah, the Qowa'idul Lughoh Al-'Arabiyyah is used as the primary teaching material. However, differences in student backgrounds and the lack of comprehensive evaluation pose challenges. This study employed descriptive qualitative research with interview, observation, and documentation techniques to evaluate teacher performance in Arabic language learning. The results showed that teachers had conducted regular and structured evaluations, but student understanding of the material remained low. While seventy percent of students generally understood the material, only sixty percent demonstrated in-depth understanding. This situation forced teachers to repeat the material, which resulted in delays in achieving learning targets. Therefore, additional strategies such as more contextual learning and increased use of Arabic in students' daily activities are needed.